Hubungan Tingkat Stres Mahasiswa Tingkat 2 dan 3 Fakultas Kedokteran Unisba dengan Hasil Kelulusan Ujian Lisan secara Online - Muhammad Rian Alvagus; Muhammad Nurhalim Shahib; Rizki Perdana (Bandung Conference Series: Medical Science, 2022)
Abstract. Stress is the inability to face physical, mental, emotional, and psychological threats that can interfere with the education process. Medical students undergo several types of exams that can cause stress. The Covid-19 pandemic has caused students to carry out oral exams using an online method so that it can be an additional stressor in lectures. This study aims to see the relationship between the stress level of Unisba Medical Faculty students with the results of passing the online oral exam. Methods: The research design used was cross sectional. Student stress levels were measured using the DASS-42 questionnaire and data on the results of online oral exams were recorded after the exam took place. Results: The stress levels experienced by students were normal stress (75.63%), mild stress (6.72%), moderate stress (7.56%), severe stress (3.36%), and very heavy stress (6 ,72%). The results of student graduation obtained are passing (88.24%) and not passing (11.76%). There was no relationship between student stress levels and the results of online oral exams (p=0.684 for level 2 and p=0.156 for level 3). Conclusion: There is no relationship between student stress levels and online oral exam results. Further research needs to look for other causes that can cause stress in medical students and need to analyze in detail the cognitive, affective, and psychomotor levels. Abstrak. Stres adalah ketidakmampuan menghadapi ancaman fisik, mental, emosional, dan psikologis yang dapat mengganggu proses Pendidikan. Mahasiswa kedokteran menjalani beberapa jenis ujian yang dapat menyebabkan stres. Pandemi Covid-19 menyebabkan mahasiswa melaksanakan ujian lisan dengan metode online sehingga dapat menjadi salah satu stresor tambahan dalam perkuliahan. Penelitian ini bertujuan untuk melihat hubungan tingkat stres mahasiswa Fakultas Kedokteran Unisba dengan hasil kelulusan ujian lisan secara online. Metode: Desain penelitian yang digunakan adaah cross sectional. Tingkat stres mahasiswa diukur menggunakan kuesioner DASS-42 dan data hasil kelulusan ujian lisan secara online didata setelah ujian berlangsung. Hasil: Tingkat stres yang dialami mahasiswa adalah stres normal (75,63%), stres ringan (6,72%), stres sedang (7,56%), stres berat (3,36%), dan stres sangat berat (6,72%). Hasil kelulusan mahasiswa yang didapatkan yaitu lulus sebesar (88,24%) dan tidak lulus sebesar (11,76%). Tidak terdapat hubungan tingkat stres mahasiswa dengan hasil kelulusan ujian lisan secara online (p=0,684 untuk tingkat 2 dan p=0,156 untuk tingkat 3). Kesimpulan: Tidak terdapat hubungan tingkat stres mahasiswa dengan hasil kelulusan ujian lisan secara online. Penelitian lanjutan perlu mencari penyebab lain yang dapat menyebabkan stres mahasiswa kedokteran dan perlu menganalisis secara mendetail tentang tingkatan kognitif, afektif, dan psikomotor.